2022
DOI: 10.3390/agronomy12092223
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Inoculation Improves the Quality and Productivity of Essential Oil Distilled from Three Aromatic and Medicinal Plants: Thymus satureioides, Thymus pallidus, and Lavandula dentata

Abstract: In Morocco, extensive use, traditional practices, and climate change have seriously impacted the productivity of aromatic and medicinal plants (AMP). To mitigate these adverse effects, this study aims at evaluating the potential of the arbuscular mycorrhizal fungi (AMF), namely Rhizophagus irregularis and Funneliformis mosseae, in improving biomass, essential oils (EOs), and biomolecule production in Thymus satureioides, T. pallidus, and Lavandula dentata. Compared to non-inoculated-AMP, AMF induced significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Regardless of the Pb and Cd stress, mycorrhization with G. intraradices enhanced the essential oil yield in M. x piperita , in which mycorrhizal plants showed higher yield than non‐mycorrhizal plants (Figure 1). In agreement with our results, several previous studies [1,4,46,54–71] reported that mycorhization with arbuscular mycorrhizal fungi significantly improved the essential oil yield of medicinal and aromatic plants, such as Anethum graveolens, Trachyspermum ammi, Coriandrum sativum, Mentha arvensis, Mentha piperita, Ocimum basilicum, Mentha viridis, Mentha crispa , Thymus satureioides, Thymus pallidus , Lavandula dentata, Corianderum sativum , Atractylodes lancea , Inula ensifolia , Artemisia umbelliformis , Plectranthus amboinicus , Satureja macrostema , Salvia officinalis , Origanum vulgare, Origanum onites , Thymus daenensis , Thymus vulgaris and Foeniculum vulgare .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Regardless of the Pb and Cd stress, mycorrhization with G. intraradices enhanced the essential oil yield in M. x piperita , in which mycorrhizal plants showed higher yield than non‐mycorrhizal plants (Figure 1). In agreement with our results, several previous studies [1,4,46,54–71] reported that mycorhization with arbuscular mycorrhizal fungi significantly improved the essential oil yield of medicinal and aromatic plants, such as Anethum graveolens, Trachyspermum ammi, Coriandrum sativum, Mentha arvensis, Mentha piperita, Ocimum basilicum, Mentha viridis, Mentha crispa , Thymus satureioides, Thymus pallidus , Lavandula dentata, Corianderum sativum , Atractylodes lancea , Inula ensifolia , Artemisia umbelliformis , Plectranthus amboinicus , Satureja macrostema , Salvia officinalis , Origanum vulgare, Origanum onites , Thymus daenensis , Thymus vulgaris and Foeniculum vulgare .…”
Section: Resultssupporting
confidence: 93%
“…Similar to our results, there are several reports in which mycorrhization resulted in improved concentration of essential oil components; e. g ., limonene and carvone in Anethum graveolens , thymol in Trachyspermum ammi , anethol in Foeniculum vulgare , geraniol and linalool in Coriandrum sativum , [1–3] menthol in Mentha arvensis , [56] forskolin in Coleus forskohlii , [4] α‐terpineol in Ocimum basilicum , [57] artemisinin in Artemisia annua , [5,6] carvacrol in Origanum vulgare , [76] bornyl acetate, 1,8‐cineole, α‐ thujones and β ‐thujones in Salvia officinalis , [77] limonene, 1,8 cineole, carvone, eugenol and (E) ‐methyl cinnamate in Mentha viridis , [62] carvacrol, linalool, thymol, β ‐caryophyllene, carvacrol methyl ether, terpinene‐4‐ol and borneol in Thymus satureioides , β ‐caryophyllene, α‐ terpinene, (+)‐4‐carene, γ ‐terpinene, camphene, verbenene and terpinen‐4‐ol in Thymus pallidus , tricyclene, D‐limonene, germacrene D, L‐fenchone, β ‐eudesmol, bornyl acetate, carveol and camphor in Lavandula dentata [71] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AMF-S and AMF-C showed the best results (Popescu & Popescu, 2022). Similar results have been obtained in other studies ( Binet et al, 2020, Pirsarandib et al, 2022, in particular, a positive effect on the composition of essential oils during AMF treatment was found (Akachoud et al, 2022). This indicates the feasibility of conducting research in this area to increase the efficiency of lavender cultivation in the Southern Steppe of Ukraine and reduce the impact of drought on plant growth and development and the quality content of essential oils.…”
Section: Discussionsupporting
confidence: 86%
“…Anthocyanins, carotenoids and other phenolic compounds are increased in lettuce in response to Rhizophagus fasciculatus, R. irregularis and Funneliformis mosseae inoculations [103]. AMF can also boost essential oil yields in medicinal and aromatic plants and improve their composition in terpenoids and flavonoids [104][105][106]. For all these reasons, mycorrhizal inoculation is becoming an agronomic tool among biofertilizers and plant biostimulants [107][108][109][110].…”
Section: Plant Growth and Yield Improvementsmentioning
confidence: 99%